2021
DOI: 10.3390/nu13113705
|View full text |Cite
|
Sign up to set email alerts
|

Anemia of School-Age Children in Primary Schools in Southern China Should Be Paid More Attention despite the Significant Improvement at National Level: Based on Chinese Nutrition and Health Surveillance Data (2016–2017)

Abstract: Globally, anemia among school-age children (SAC) remains a serious public health problem, impacting their growth, development, educational attainment and future learning potential. National and subnational anemia prevalence among SAC in China has not been assessed recently. Based on data from Chinese Nutrition and Health Surveillance (2016–2017), the current anemia status of SAC in primary schools in China was investigated. Anemia prevalence of SAC in primary schools in China was 4.4%, dropping 63.6% compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(47 reference statements)
0
3
1
1
Order By: Relevance
“…Te magnitude of anemia in this study is higher than that in a study conducted in Northwest Ethiopia (7.6%) [41], Durbete Town, Northwest Ethiopia (10.7%) [29], and China (8.4%) [27]. Te discrepancy may be attributed to the diferences in socioeconomic, sociodemographic, and cultural behaviors, studied population, and study period and setting.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Te magnitude of anemia in this study is higher than that in a study conducted in Northwest Ethiopia (7.6%) [41], Durbete Town, Northwest Ethiopia (10.7%) [29], and China (8.4%) [27]. Te discrepancy may be attributed to the diferences in socioeconomic, sociodemographic, and cultural behaviors, studied population, and study period and setting.…”
Section: Discussioncontrasting
confidence: 80%
“…Studies conducted in Ethiopia documented that factors that afect anemia in school-age children were mother occupation status, father occupation status, maternal education, father education, family size, parasites in the stool, stunted, and underweight [12,15,16,[24][25][26][27][28][29]. Te Ethiopian government has been working to address the nutritional concerns of SAC, mainly by integrating nutritionally sensitive interventions such as conducting regular monitoring of the nutritional status of school-age children/students together with biannual deworming and water hygiene and sanitation (WASH) programs in schools [30], mass fortifcation of staple foods and condiments, home (point-of-use) fortifcation of foods, initiating a homegrown school feeding program for school-aged children, and provision of micronutrient supplements and weekly iron and folic acid supplementation (WIFAS) [19,31].…”
Section: Introductionmentioning
confidence: 99%
“…Tis study showed that the prevalence of anemia is 6.52% in Chinese Grade 4 students, which is similar to the results of other current national surveys on the prevalence of anemia in China. Te China Nutrition and Health Surveillance data showed that the prevalence of anemia was 4.01% and 3.25% in children aged 10 and 11 years, respectively [33]. Data from the Chinese National Survey on Student Constitution and Health revealed that the prevalence of anemia in children aged 9 and 12 years was 6.8% and 9.6%, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the prevalence of anemia is 6.52% in Chinese Grade 4 students, which is similar to the results of other current national surveys on the prevalence of anemia in China. The China Nutrition and Health Surveillance data showed that the prevalence of anemia was 4.01% and 3.25% in children aged 10 and 11 years, respectively 14 . Data from the Chinese National Survey on Student Constitution and Health revealed that the prevalence of anemia in children aged 9 and 12 years was 6.8% and 9.6%, respectively 2 .…”
Section: Discussionmentioning
confidence: 99%